Numerical analysis of 3D printed joint of wooden structures regarding mechanical and fatigue behaviour - Petr Lehner; Premysl Parenica; David Juracka; Martin Krejsa (Fracture and Structural Integrity)
This paper presents numerical models of a 3D printed plastic joint applicable to the connection of wooden structures. The research presented provides a comparison of two alternative solutions for the geometry of the joint and results from several loading schemes and boundary conditions. Included are analyses evaluating the mechanical behaviour in a simple axial tensile test, a three-point bending test and, finally, a sensitivity analysis of the location susceptible to fatigue damage. The models include a 3D printed polycarbonate joint, wooden elements and steel shear pins. The combined model allows a deeper understanding of the interactions. Finite element method (FEM) software was used to develop the numerical models and suitably defined boundary conditions, and material properties of all parts were adopted. The simulation results show that the 3D joint exhibits a high resistance to tensile loading, while in the case of three-point bending, a higher susceptibility to fracture of the printed joint is observed. The sensitivity fatigue analysis identified critical areas on the 3D printed component that need to be improved before further development. These analyses provide important information for optimizing the design of 3D printed plastic joints intended for wooden structures